Evidence of a magnetic transition in atomically thin Cr2TiC2Tx MXene. Issue 12 (22nd October 2020) - Hantanasirisakul, Kanit; Anasori, Babak; Nemsak, Slavomir; Hart, James L.; Wu, Jiabin; Yang, Yizhou; Chopdekar, Rajesh V.; Shafer, Padraic; May, Andrew F.; Moon, Eun Ju; Zhou, Jun; Zhang, Qinghua; et al.
Abstract : Evidence for a magnetic transition in atomically thin chromium titanium carbide MXene (Cr2 TiC2 T x ) has been shown experimentally using a combination of magnetometry, spectroscopy, and magnetotransport measurements. Abstract : Two-dimensional (2D) transition metal carbides and nitrides known as MXenes have shown attractive functionalities such as high electronic conductivity, a wide range of optical properties, versatile transition metal and surface chemistry, and solution processability. Although extensively studied computationally, the magnetic properties of this large family of 2D materials await experimental exploration. 2D magnetic materials have recently attracted significant interest as model systems to understand low-dimensional magnetism and for potential spintronic applications. Here, we report on synthesis of Cr2 TiC2 T x MXene and a detailed study of its magnetic as well as electronic properties. Using a combination of magnetometry, synchrotron X-ray linear dichroism, and field- and angular-dependent magnetoresistance measurements, we find clear evidence of a magnetic transition in Cr2 TiC2 T x at approximately 30 K, which is not present in its bulk layered carbide counterpart (Cr2 TiAlC2 MAX phase). This work presents the first experimental evidence of a magnetic transition in a MXene material and provides an exciting opportunity to explore magnetism in this large family of 2D materials.